2022
DOI: 10.1093/nar/gkac421
|View full text |Cite
|
Sign up to set email alerts
|

Structures of nonsense-mediated mRNA decay factors UPF3B and UPF3A in complex with UPF2 reveal molecular basis for competitive binding and for neurodevelopmental disorder-causing mutation

Abstract: UPF3 is a key nonsense-mediated mRNA decay (NMD) factor required for mRNA surveillance and eukaryotic gene expression regulation. UPF3 exists as two paralogs (A and B) which are differentially expressed depending on cell type and developmental stage and believed to regulate NMD activity based on cellular requirements. UPF3B mutations cause intellectual disability. The underlying molecular mechanisms remain elusive, as many of the mutations lie in the poorly characterized middle-domain of UPF3B. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…The authors performed fluorescence anisotropy experiments and reported affinities in the low nanomolar range for UPF2 MIF4G domains 1-2, as well as MIF4G domain 3 with the U1BD [ 53 ]. This corroborates previous work showing that UPF2′s MIF4G domain 3 binds RNA in electrophoretic mobility shift assays (EMSAs) via conserved basic and aromatic residues [ 112 ] and work showing ribosome and RNA binding of UPF2 in complex with UPF3B [ 113 , 114 ]. In complex with UPF1, UPF2 was shown to help UPF1-RNA dissociation, likely by binding to a region allosteric of UPF1’s RNA-binding site [ 53 ].…”
Section: Core Nmd Factorssupporting
confidence: 90%
See 4 more Smart Citations
“…The authors performed fluorescence anisotropy experiments and reported affinities in the low nanomolar range for UPF2 MIF4G domains 1-2, as well as MIF4G domain 3 with the U1BD [ 53 ]. This corroborates previous work showing that UPF2′s MIF4G domain 3 binds RNA in electrophoretic mobility shift assays (EMSAs) via conserved basic and aromatic residues [ 112 ] and work showing ribosome and RNA binding of UPF2 in complex with UPF3B [ 113 , 114 ]. In complex with UPF1, UPF2 was shown to help UPF1-RNA dissociation, likely by binding to a region allosteric of UPF1’s RNA-binding site [ 53 ].…”
Section: Core Nmd Factorssupporting
confidence: 90%
“…UPF3B is a nucleocytoplasmic shuttling protein which binds to the EJC in the nucleus and is then exported to the cytoplasm in complex with the EJC [ 5 ]. Human UPF3B comprises an RNA recognition motif-like (RRM-L) domain in its N-terminal, followed by a NONA/paraspeckle-like (NOPS-L) region, two predicted coiled-coil-like (CCL-1 and CCL-2) regions and a C-terminal EJC-binding motif (EBM) ( Figure 4 ) [ 114 ].…”
Section: Core Nmd Factorsmentioning
confidence: 99%
See 3 more Smart Citations